The Impacts of Changes in Business Field Structure on Income Disparity - Fath Fauzan Falaq; Bintoro, Nugroho Suryo (Journal of Development Economic and Social Studies, 2025)
Income inequality could significantly affect a country’s economic development. Therefore, Reduced Inequality has become one of Sustainable Development Goals (SGDs). However, according to the Sustainable Development Report’s website Indonesia’s effort in reducing inequality is still stagnant, this is supported by Indonesia Central Agency of Statistic (BPS) which shows Indonesia’s Gini Ratio is stagnant at 0.38 from 2018 to 2023. Simon Kuznets theorized that income inequality could be the consequence of economic growth that was triggered by the change in the economic sector from traditional to modern. The goal of this research is to analyze the effect of economic structural change, economic growth, and average school duration on income inequality in rural, urban, and all of Indonesia from the implementation of SGDs in 2015 to 2023 using panel data regression in 34 provinces in Indonesia. This research found that agriculture, industry and service sector growth, and mean years of schooling significantly affected income inequality in rural areas, but agriculture sector growth and economic growth sector did not significantly affect income inequality in rural areas.